The Effect of Fintech Adoption, Financial Literacy and Financial Management Behavior to MSME Performance in Medan - Amaliani, Fitri; Muliyani, Muliyani (Program Pascasarjana STIE Amkop Makassar, 2024)
This study aims to analyze the influence of fintech, financial literacy and financial management behavior on MSME performance. This study used a quantitative research design using statistical testing methods based on statistical tests.Data collection is carried out through the distribution of offline and online questionnaires to MSME players who use fintech payment methods in the form of